Low-cost male urogenital simulator for penile implant surgery training: a 3D printing approach - Zixi Wang; Carlo Saija; Nicholas Raison; Abdullatif Aydin; Zhouyang Xu; Katie Zuo; Kawal Rhode; Antonia Pontiki (3D Printing in Medicine)
Abstract Background Penile implant surgery is the standard surgical treatment for end-stage erectile dysfunction. However, the growing complexity of modern high-tech penile prostheses has increased the demand for more practical training opportunities. The most advanced contemporary training methods involve simulation training using cadavers, with costs exceeding $5,000 per cadaver, inclusive of biohazard fees. This study introduces an innovative and cost-efficient male urogenital simulator designed to enhance penile implant surgery training. Methods Utilizing image segmentation of patient pre-operative computed tomography (CT) scans, combined with three-dimensional (3D) printing and silicone molding techniques, we developed a high-fidelity simulator replicating the anatomical structures of the male urogenital system. The simulator incorporates an innovative double-layer structural design encompassing the corpus spongiosum and glans, corpora cavernosa, testes, epididymides, and pelvic bones. Additionally, it utilizes a two-stage skin manufacturing process tailored for different skin regions. The simulator was produced at a low material cost of £10, with an average production time of 3 h. To evaluate its training efficacy, we conducted a penile implant surgery training session involving 15 urology trainees and surgeons ranging from specialty training levels ST3 to ST6. The session began with a demonstration of penile implant surgery and error detection. Trainees, averaging three per simulator, practiced corporotomy, dilation, measurement, penile prosthesis, and scrotal pump placement under expert guidance. Participants’ feedback was collected using a Likert scale questionnaire, assessing learning, satisfaction, and anatomical accuracy. Results Quantitative analysis of the questionnaire responses indicated highly positive feedback from the participants. Satisfaction rates surpassed 96% in learning effectiveness, over 89% in overall satisfaction, and 86% in anatomical accuracy demonstration. The simulator was favourably reviewed by both urology trainees and experienced surgeons, highlighting its utility as a practical training tool. Its low production cost and high precision make it a viable alternative to current training models. Conclusions The development of this cost-efficient, anatomically accurate urogenital simulator through advanced imaging and additive manufacturing techniques represents a significant advancement in penile implant surgical training. This state-of-the-art simulator not only provides a realistic and practical training experience but also underscores the potential for 3D printing technologies to revolutionize medical education and training.